PENGARUH SUPERVISI PADA PSIKOLOGI PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN SMP NEGERI 02 DESA LUBUK PALAS - Utami, Maya Rizky; Syafira; Hasanah, Uswatun; Utami, Nuria Tri; Apulina, Sri; Gusriana, Anggi (Yayasan Pendidikan Islam Akmalia, 2022)
This study aims to determine the implementation of academic supervision of school supervisors, supervision of school principals, teacher performance, as well as to determine the effect of the implementation of supervision on educational psychology in improving the quality of education at SMP Negeri Lubuk Palas village. The type of research used is descriptive qualitative, with a phenomenological approach to interpret the phenomena that occur where the researcher is the instrument, the sampling of data sources is carried out by data collection techniques in the form of interviews. Respondents in this study were principals and teachers. The analysis used descriptive analysis and inferential analysis. The results of the descriptive analysis showed that the implementation of the academic supervision of the school supervisor was quite good, the supervision of the principal was carried out well and in the high category and the teacher's performance was carried out well and in the high category. The results of inferential analysis using linear regression show that: (1) the competence of school supervisors' academic supervision has a significant effect on the quality of education, (2) the supervision of principals has a significant effect on the quality of education, (3) the competence of school supervisors' academic supervision and supervision of school principals simultaneously equally significant effect on the quality of educatio